Assistance in the Management of Entrepreneurship-Based Nonformal Educational Institutions and Institutional Digital Marketing - Wiwin - Yulianingsih; Gunarti Dwi Lestari; Soedjarwo Soedjarwo; I Ketut Atmaja; Shobri Firman Susanto; Mita - Lutviatiani (Universitas Negeri Padang, 2023)
The low knowledge and interest of the community to glance at the existence of Community Learning Centers (CLC) as non-formal educational institutions is often a problem for administrators to maintain the existence of non-formal education in the community. Therefore, it is necessary to assist in the management of non-formal educational institutions based on entrepreneurship and digital marketing as a self-branding effort for community learning center institutions. This activity was carried out by applying training and mentoring methods which were carried out in several stages, namely identification and survey, followed by socialization and implementation, the activity stage, and the last stage was evaluation. This activity was carried out at the Budi Utama Community Learning Center in Surabaya, and attended by managers of non-formal educational institutions throughout the city of Surabaya. The results obtained from this activity were seen through the performance of the speakers, target participants, participants' abilities after mentoring, and the implementation of post-coaching skills by the managers, and overall satisfactory results were obtained and the assisting participating institutions could implement the material well in managing their institutions. So, it can be concluded that this activity can be carried out as an effort to develop potential while increasing the income of CLC institutions so that institutions can experience financial development.